'Spin' in reports of clinical research. Issue 6 (13th October 2016) - Mahtani, Kamal R
Abstract : Clinical research is frequently hampered by flaws in its design or conduct. Such biases have been well documented. However, reports of clinical research may also be biased and present results in a more favourable way than they deserve or downplay harms. Such 'spin' in reporting has been demonstrated empirically. This short commentary summarises some of the problems with spin in reports of clinical research as well as signposts to some of the empirical evidence demonstrating its effect.